THE INFLUENCE OF STUDENT-CENTERED APPROACHES ON ACADEMIC ACHIEVEMENT AND ENGAGEMENT - Jahongir Javdatovich Tursunhodjaev (Bright Mind Publishing, 2025)
Student-centered approaches have become a cornerstone of modern pedagogy, emphasizing active learning, critical thinking, and learner autonomy. This study examines the influence of student-centered teaching methods on students’ academic achievement and engagement. By reviewing theoretical frameworks and empirical studies, the article highlights the advantages of participatory learning strategies, collaborative projects, and problem-based tasks in promoting deeper understanding and sustained motivation. The findings indicate that student-centered approaches enhance academic outcomes, foster critical thinking, and increase overall engagement in the learning process.
Keywords: Student-centered learning; academic achievement; student engagement; active learning; motivation; collaboration; critical thinking; education reform.